Ask me, I (Dis)agree! Acquiescence in student ratings of teaching quality in German vocational schools. (March 2021) - Marder, Johanna; Göllner, Richard; Wagner, Wolfgang; Fauth, Benjamin
Highlights: Acquiescent responding in student ratings of teaching quality (5th and 8th grade). Impact of acquiescence on teaching quality ratings more pronounced in 5th grade. Acquiescence partly explains differences in teaching quality ratings across grades. Abstract: Student ratings are frequently used to assess teaching quality even though they might be influenced by an acquiescent response style. Acquiescence is considered particularly common among young respondents and has been recognized as a source of systematic response error. Within a structural equation modeling framework, we examined whether student ratings of teaching quality provided by two age cohorts (fifth- and eighth-grade students) were affected by acquiescence, while additionally controlling for an extreme response style. Across both age cohorts, acquiescence had the highest and most consistent effects on student ratings of teaching quality, whereas extreme responding affected only ratings by fifth-grade students and to a smaller degree. Mean differences in teaching quality ratings between fifth- and eighth- grade students were partly explained by age-related differences in acquiescence. Overall, the effects of acquiescence on student ratings were rather small and primarily affected the ratings provided by younger students (i.e., fifth graders).